Impact of Temporomandibular Joint Pain in Rheumatoid Arthritis - Neveen Ahmed; Hamid Masoud Mustafa; Anca Irinel Catrina; Per Alstergren (Mediators of Inflammation)
To investigate the impact of temporomandibular joint (TMJ) pain on daily activities and quality of life in relation to systemic inflammatory activity in patients with rheumatoid arthritis (RA), thirty-three consecutive outpatients with RA were included. TMJ pain intensity at rest, on maximum mouth opening, and on chewing was assessed on a 0–10 numerical rating scale. TMJ palpatory tenderness, degree of anterior open bite, the impact of TMJ pain on daily activities and quality of life were also assessed. The systemic inflammatory activity was estimated by the disease activity score 28 (DAS28), blood levels of inflammatory markers and number of painful musculoskeletal regions. TMJ pain at rest, on maximum mouth opening, and on chewing as well as DAS28 was correlated with the impact of the TMJ pain on daily activities and quality of life. Partial correlations showed a significant interaction between TMJ pain on movement and DAS28 that explained the TMJ pain impact on daily activities and quality of life to a significant degree. This study indicates that both current TMJ pain intensity and systemic inflammatory activity play roles in the impact of TMJ pain on daily living and quality of life in RA.